Protein-Level Evidence of Novel β-Type Hemocyanin and Heterogeneous Subunit Usage in the Pacific Whiteleg Shrimp, Litopenaeus vannamei - Wang, Jason; Janech, Michael Gregory; Burnett, Karen Gray (Frontiers in Marine Science, 2019)
The functional diversity of crustacean hemocyanins is broad, encompassing O2 delivery, innate immune response, metabolite storage, and osmolyte balance, all in a heterogeneous protein structure. As such, the sequence diversity of this class of proteins and its subunit composition are the focus of many studies on crustacean adaptation to environmental challenges. Recent transcriptomic and genomic assemblies on the Pacific whiteleg shrimp Litopenaeus vannamei have identified unique isoforms of hemocyanin including an ancestral β-type subunit thought to be lost in penaeid shrimp. However, it is unknown the degree to which these isoforms are translated as proteins, and their abundances within the hemolymph. The present study uses proteomic approaches to characterize the protein-level abundance and organization of these hemocyanin isoforms within their native oligomeric structures. Fractions of each hemocyanin oligomeric form were purified by size-exclusion high performance liquid chromatography for identification of subunit isoforms using tandem mass spectrometry at <1% protein false discovery rate. Data are available via ProteomeXchange with identifier PXD014575. Relative abundances of hemocyanin oligomers and monomeric subunits from hemolymph and fractions were also quantified by polyacrylamide gel electrophoresis with and without denaturation for comparison of subunit heterogeneity. Hemocyanin subunits were organized primarily as hexamers (95-99% relative abundance) as opposed to dodecamers. Ten unique hemocyanins predicted by transcriptome and genome assemblies were identified by tandem mass spectrometry in both oligomer fractions including the first protein-level evidence of a β-type subunit in penaeid shrimp. Identified hemocyanins mapped to four genomic scaffolds and had two or three exons. A single small (75 kDa) subunit constituted half or more of all isoforms identified in each oligomer. The dodecameric fraction exhibited greater subunit heterogeneity utilizing a significantly lower ratio (1.04:1) of small subunit to large subunit compared to hexamers (2.05:1). One isoform, XP_027232115.1, appeared to be more dominant within dodecamers than hexamers. The ability to distinguish and quantify hemocyanin isoforms within oligomeric structures will aid future studies linking hemocyanin genes to transcripts to function and physiology as well as offer insight into the evolutionary history of crustaceans.